Communication Research methods in Postmodern Culture: A revisionist Approach (Global Business Management Review (GBMR), 2022)
Larry Z. Leslie, PhD, is currently Associate Professor Emeritus in the School of Mass Communications, University of South Florida, Tampa. His area of expertise lies in media ethics, communication research methods, public opinion and postmodern culture. His other works include Mass Communication Ethics: Decision Making in Postmodern Culture (2nd Ed, 2004, Pearson/ Allyn & Bacon) and Celebrity in the 21st Century: A Reference Handbook (2011, Pearson). In many institutions of higher learning, students develop a negative predisposition towards the research methodology course as mundane and tiresome and conduct researches without fully understanding or equipped with the needed skills. Students on the other hand also fail to find new realistic ways to link the interrelationship between explanations and the studied phenomenon. Thus, this book materializes from the author’s notion that traditional research methodology courses in colleges and universities need to be re-addressed from an interesting yet practical approachable manner. The postmodern cultural approach to research aims to adjust traditional methodologies and hopes to shed light into creating effective researchers who are not only thinking, but also who could design and carry-out studies effectively in an information rich, cross- cultural environment.